EFEKTIFITAS KARBON AKTIF UNTUK MENURUNKAN KADAR CO DALAM RUANGAN - Wahyudi Hutabarat (FT-USNI, 2019)
Cigarette containing more than 4000 elements and at least 200 of them noxious to health. Poison main on cigarettes are tar, nicotine, and carbon monoxide. The purpose of this study is to find the ability coconut shell, wood the mango tree and wood of trees mahogany as the adsorbent carbon monoxide. This research is pre-eksperimental to the control group random only design. The independent variable is kinds of carbon active (coconut shell, wood the mango tree, timber tree mahogany and contol), dependent variable is the concentration of carbon monoxide. The research results show concentration lowest carbon monoxide of control room and after adsorbsi use adsorbent the lowest is found in coconut shell namely 2,79 ppm. The average the percentage the decline in gas co after using adsorbent of coconut shell compared to control is 82 %, then with wood mahogany trees compared to control is 77 %, while the wood of trees manga when compared with control is 52 % percent. Decreases of gas co is highest at the adsorbent kneecap kelapa is 82 %. And then the significant differences concentration gas co after adsorbsi by various species of an adsorbent. One way the test results t independent test to see the reduction of carbon monoxide differences between all the adsorbent is 0,000. Conclusion: no distinction adsorbsi carbon monoxide on any an adsorbent.